PENGARUH DIGITALISASI LAYANAN TERHADAP BEBAN KERJA, STRES KERJA, KINERJA KARYAWAN, DAN KEBUTUHAN PELATIHAN & PENGEMBANGAN PADA BANK SYARIAH DI INDONESIA - Dewi Tri Komalasari; Dyah Ayu Siti Fatimah; Destiani Rahmawati; Ike Hilatunnisa (Islamic Banking & Economic Law Studies (I-BEST), 2026)
This study examines the influence of service digitalization on workload, work stress, employee performance, and training and development needs in Indonesian Islamic banking through a qualitative library research approach. The findings reveal that service digitalization fundamentally transforms the workload structure of Islamic bank employees, where automation reduces repetitive administrative tasks but simultaneously generates new and more cognitively demanding work requirements. This workload transformation subsequently contributes to elevated levels of work stress, manifesting through technostress, job insecurity, and always-on culture as direct consequences of digital ecosystem adoption. Furthermore, service digitalization is proven to significantly drive the increasing need for employee training and development, particularly in mastering digital competencies that remain aligned with Islamic principles a unique demand that distinguishes Islamic banks from their conventional counterparts. Unmanaged work stress demonstrably impairs employee performance across multiple dimensions, including service quality, productivity, and innovative contribution. Moreover, work stress functions as a significant mediating variable in the relationship between service digitalization and employee performance. These findings underscore that successful digital transformation in Islamic banking requires a holistic human resource management approach that simultaneously develops digital competencies, fulfills structured training and development needs, while preserving employee psychological well-being.